2015
DOI: 10.1038/ctg.2015.30
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Symptoms Are Common and Benefit from Biofeedback Therapy in Patients with Dyssynergic Defecation

Abstract: Objectives:Dyssynergic defecation (DD) is a subtype of chronic constipation that responds to biofeedback therapy (BFT). Abdominal, anorectal, and stool symptoms are commonly reported by DD patients, but limited data exist to demonstrate the improvement of these associated symptoms to BFT. Aims to prospectively study the response of constipation and associated abdominal, rectal, and stool symptoms to biofeedback in a population with dyssynergia.Methods:Patients with DD as determined by anorectal manometry and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…Dyssynergia is a defecatory disorder characterized by increased anal sphincter pressure (i.e., anal contraction; Table 1 ) for which biofeedback—using visual or auditory cues to improve muscle control—is efficacious [ 38 , 45 ]. It is important to ascertain whether the patient has intermittent constipation or solid stools, in which case, diarrhea may reflect an “overflow” phenomenon.…”
Section: Comorbid Disorders: Testing To Exclude Ibsmentioning
confidence: 99%
“…Dyssynergia is a defecatory disorder characterized by increased anal sphincter pressure (i.e., anal contraction; Table 1 ) for which biofeedback—using visual or auditory cues to improve muscle control—is efficacious [ 38 , 45 ]. It is important to ascertain whether the patient has intermittent constipation or solid stools, in which case, diarrhea may reflect an “overflow” phenomenon.…”
Section: Comorbid Disorders: Testing To Exclude Ibsmentioning
confidence: 99%
“…Biofeedback is helpful in improving pelvic floor muscle strength in patients with low tone but is also used effectively in treatment of anismus or pelvic floor dyssynergia. A 2015 study showed a 48% improvement in patient symptom scores using the patient assessment of constipation-symptoms (PAC-SYM) questionnaire following 6-8 sessions of biofeedback therapy with manual and verbal biofeedback, surface electromyography (EMG), rectal balloon sensory therapy, pelvic floor and abdominal massage and core strengthening to correct dyssynergia [40].…”
Section: The Role Of Physical Therapy In Treatment Of Constipationmentioning
confidence: 99%
“…una maniobra defecatoria coordinada, contracción abdominal adecuada, relajación anal y mejorar la percepción rectal 8,9 . Existen estudios comparativos en los que la rehabilitación es superior a placebo, dieta, otras técnicas de biofeedback simulado, diazepam y laxantes consiguiendo unos resultados favorables en el 50-86% pacientes según los estudios y con una media 69%.…”
Section: Revisiones Temáticasunclassified